2022
DOI: 10.1177/00469580221093442
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the SARS-CoV-2 Virus on the Cardiovascular System and Coagulation State Leading to Cardiovascular Diseases: A Narrative Review

Abstract: The novel coronavirus pandemic has led to morbidity and mortality throughout the world. Until now, it is a highly virulent contagion attacking the respiratory system in humans, especially people with chronic diseases and the elderly who are most vulnerable. A majority of afflicted are those suffering from cardiovascular and coronary diseases. In this review article, an attempt has been made to discuss and thoroughly review the mode of therapies that alleviate cardiac complications and complications due to hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 77 publications
(117 reference statements)
0
5
0
2
Order By: Relevance
“…Hypotension is an important mechanism of prerenal kidney injury in COVID‐19 patients, and may be caused by fever, sepsis, dehydration caused by diarrhea and vomiting, myocarditis, right heart failure leading to hemodynamic instability, and renal venous congestion 43–46 . Furthermore, prerenal kidney injury may also be caused by the high positive end‐expiratory pressure levels required for mechanical ventilation 47 .…”
Section: Mechanisms Related To Indirect Damagementioning
confidence: 99%
“…Hypotension is an important mechanism of prerenal kidney injury in COVID‐19 patients, and may be caused by fever, sepsis, dehydration caused by diarrhea and vomiting, myocarditis, right heart failure leading to hemodynamic instability, and renal venous congestion 43–46 . Furthermore, prerenal kidney injury may also be caused by the high positive end‐expiratory pressure levels required for mechanical ventilation 47 .…”
Section: Mechanisms Related To Indirect Damagementioning
confidence: 99%
“…The wide distribution of COVID-19 nucleic acid in respiratory tract, saliva, feces, and breastmilk indicates that direct viral attack to the target cells may be an alternative reason (Lymperopoulos et al, 2021). Angiotensin-converting enzyme 2 (ACE2) is a receptor providing the main entry site for SARS-CoV to invade human cells, and this in turn facilitates direct damage of virus through the course of infection (Bhat et al, 2022.). recently reported that ACE2 was highly expressed in the heart (Vineis et al, 2019), ACE2 is more than a critical gateway for SARS-COV2 entry, it's also the functional disruption of it and can cause the loss of cardiopulmonary homeostasis during COVID-19 (Al-Kindi & Zidar, 2022).…”
Section: Parametersmentioning
confidence: 99%
“…Postmortem studies in patients with COVID-19 revealed cardiac hypertrophy, right ventricular dilatation and evidence of right ventricular involvement (19%), lymphocytic myocarditis (14%-40%), focal pericarditis (19%), endocardial thrombosis (14%) or endothelitis, and small vessel thrombosis (19%) [7][8][9] . The high expression of ACE2 in cardiomyocytes renders them susceptible to injury by SARS-Cov-2 [10][11][12] . SARS-Cov-2 infection produces cytotoxic effects, activates the innate immunity (eg, interferon signal transduction, apoptosis, reactive oxygen stress [ROS] and antiviral pathways) [13] , inhibits metabolic pathways and suppresses ACE2 expression.…”
Section: Introductionmentioning
confidence: 99%